Specimen acquisition training with a new biosimulator in endobronchial ultrasound-guided transbronchial needle aspiration. Issue 13 (March 2017) - Nakajima, Takahiro; Fujiwara, Taiki; Saegusa, Fumie; Inage, Terunaga; Sakairi, Yuichi; Wada, Hironobu; Suzuki, Hidemi; Iwata, Takekazu; Yoshida, Shigetoshi; Nakatani, Yukio; Yoshino, Ichiro
Abstract : Abstract: Training for endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) has focused on the procedure itself; however, the techniques for obtaining adequate sample are also important for achieving a pathological diagnosis as well as for molecular testing. The aim of this study was to evaluate the feasibility and efficacy of a biosimulator for training subjects in adequate sample acquisition during EBUS-TBNA. A total of 19 bronchoscopists voluntarily participated in this study. A biosimulator (ArtiCHEST, HARADA Corporation, Tokyo, Japan) was used for the training. After a 10-minute briefing, the first pass was performed by pairs of trainees. The trainees then received a 30-minute lecture that focused on the acquisition of samples using EBUS-TBNA. The trainees next performed their second pass under the supervision of the trainers. Each participant obtained a cytological smear that was coded and evaluated for quantity as well as quality by an independent cytotechnologist. The trainees had an average of 5.9 years of bronchoscopy experience. With regard to the quantity evaluation, 9 (47.4%) subjects sampled a greater number of lymphocytes on the second pass than on the first, whereas 2 were better on the first pass, and the others sampled roughly the same amount both times. With regard to the quality assessment, 9 (47.4%) subjects obtained better quality samples on the second pass, whereas the quality of the first and second pass was deemed to be roughly the same for the remaining subjects. A biosimulator can be used to train doctors in specimen acquisition and evaluate their skills with sampling using EBUS-TBNA. Abstract : Supplemental Digital Content is available in the text